Predictors of mHealth use in promoting adherence to pre-exposure prophylaxis among female sex workers: an evaluation of the Jichunge intervention in Dar es Salaam, Tanzania - Christopher Mbotwa; Method Kazaura; Kåre Moen; Melkizedeck Leshabari; Emmy Metta; Germana Leyna; Elia J. Mmbaga (BMC, 2022)
Abstract Background There is evidence that pre-exposure prophylaxis (PrEP) is effective in preventing HIV transmission, and PrEP is recommended by the World Health organization (WHO) for use by individuals at high risk of HIV infection. However, low adherence has been reported to hamper its effectiveness. Some evidence indicates that mHealth interventions may be a promising way of promoting PrEP adherence. Nevertheless, evaluations of mHealth interventions in Africa, the region most affected by HIV, are scarce. This study aimed at identifying the extent of and predictors for use of a smartphone based mHealth application among female sex workers in Dar es Salaam, Tanzania. Methods As part of a quasi-experimental study in Tanzania, 470 female sex workers who were eligible for PrEP and who owned a smartphone were recruited using respondent driven sampling. All participants were provided with an mHealth application called Jichunge, a smartphone-based app designed to promote adherence to PrEP by offering users information, advise and support during start-up and use of PrEP. We collected data through structured interviews at baseline and extracted user data from the app for a period of 30 days. Modified Poisson regression model with robust standard errors was used to identify predictors for the optimal use of the Jichunge app. Results Overall, the optimal use of the Jichunge app was 46.4%. Optimal use was significantly higher among women who were older (aPR = 1.3, 95% CI: 1.10-1.65, p = 0.004 for age 25-34 years, and aPR = 1.6, 95% CI: 1.19-2.07, p = 0.001 for age at least 35 years), who had secondary education or higher (aPR = 1.8, 95% CI: 1.08-2.94, p = 0.023), who had suboptimal social support (aPR = 1.2, 95% CI: 1.02-1.48, p = 0.030), who had high awareness of PrEP (aPR = 1.3, 95% CI: 1.08-1.55, p = 0.005), and who had experience using common mainstream social media applications (aPR = 1.4, 95% CI: 1.08-1.71, p = 0.009). Conclusion Optimal use of the Jichunge app was substantially higher among women with higher age, higher education, higher PrEP awareness, less social support, and experience using common social media applications. Individual and interpersonal factors should be considered in planning mHealth interventions. Further studies to determine predictors of longer-term mHealth engagement are needed. Trial registration International Clinical Trials Registry Platform PACTR202003823226570 ; 04.03.2020.